Optimised Spintronic Emitters of Terahertz Radiation for Time-Domain Spectroscopy - Wagner, Ford M.; Melnikas, Simas; Cramer, Joel; Damry, Djamshid A.; Xia, Chelsea Q.; Peng, Kun; Jakob, Gerhard; Klaeui, Mathias; Kicas, Simonas; Johnston, Michael B. (Journal of Infrared, Millimeter, and Terahertz Waves, 2023)
Spintronic metal thin films excited by femtosecond laser pulses have recently emerged as excellent broadband sources of terahertz (THz) radiation. Unfortunately, these emitters transmit a significant proportion of the incident excitation laser, which causes two issues: first, the transmitted light can interfere with measurements and so must be attenuated; second, the transmitted light is effectively wasted as it does not drive further THz generation. Here, we address both issues with the inclusion of a high-reflectivity (HR) coating made from alternating layers of SiO2 and Ta2O5. Emitters with the HR coating transmit less than 0.1% of the incident excitation pulse. Additionally, we find that the HR coating increases the peak THz signal by roughly 35%, whereas alternative attenuating elements, such as cellulose nitrate films, reduce the THz signal. To further improve the emission, we study the inclusion of an anti-reflective coating to the HR-coated emitters and find the peak THz signal is enhanced by a further 4%.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Reflective coatings; Spintronic; Spintronic emitters; Terahertz; THz-TDS